Pengaruh Kepuasan Kerja dan Loyalitas Karyawan Terhadap Kinerja Karyawan Pada CV. Archipelago Exports Cirebon - Muangsal; Suharti, Lilis; Rizky, Dwi Ambar (EKOBIMA, 2024)
This study aims to determine: 1) Does job satisfaction have a significant positive effect on employee performance at CV. Archipelago Exports Cirebon 2) Does employee loyalty have a significant positive effect on employee performance at CV. Archipelago Exports Cirebon 3) Do job satisfaction and employee loyalty have a positive and significant effect on employee performance at CV. Archipelago Exports Cirebon. This study is a causal associative study, namely a study that connects two or more variables. The sample or respondents in this study were employees of CV. Archipelago Exports Cirebon totaling 115 employees with the sampling technique in this study being the probability sampling technique. The sample calculation uses the Slovin formula with a sample of 115 employees and an error level of 0.01, so the sample in this study is 53 employees. Data collection using a questionnaire that has been tested for validity and reliability. The data analysis technique was carried out using multiple linear regression analysis. He results of the t-test show that job satisfaction has a positive and significant effect on employee performance. he results of the t-test show that employee loyalty has a positive and significant effect on employee performance. The results of the F test show that the variables of job satisfaction and employee loyalty have a significant and simultaneous influence on employee performance.